Demand Curves by Personal Estimate - Gilboy, Elizabeth Waterman (Quarterly Journal of Economics, 1932)
Journal Article Demand Curves by Personal Estimate Get access Elizabeth Waterman Gilboy Elizabeth Waterman Gilboy Harvard University, Committee on Economic Research Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 2, February 1932, Pages 376–384, https://doi.org/10.2307/1883236 Published: 01 February 1932